A Bibliometric analysis of green sukuk literature - Prayogo, Syamsi Mustofa Singgih; Raditya, Aji; Sarea, Adel (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – The objective of this study is to provide a comprehensive analysis of the current body of literature on green sukuk.Methodology – To achieve this objective, this study uses a bibliometric analysis and visualization and mapping of green sukuk research from to 2015-2023. The process of retrieving data through the Scopus database with the keywords "green sukuk" OR "global green sukuk" OR "retail green sukuk" OR "project based green sukuk.” Findings – The findings included the identification of the most pertinent journals, highly cited articles, prominent authors, nations with prolific publishing in green sukuk, top research affiliations, and journal quality. The study also highlights the fundamental factors that contribute to the emergence of green sukuk, such as the incorporation of Islamic finance principles, adherence to green bond standards, emphasis on sustainability, implementation of environmental, social, and governance (ESG) principles, and the desire of investors to buy such instruments. Implications – This study examines the effects of government policies on the issuance of green sukuk to support all 2030 Sustainable Development Goals (SDGs) programs, particularly in mitigating and preventing the negative effects of climate change. Furthermore, it examines the potential consequences for future studies, as other scholars can use the discoveries of this analysis to investigate new research prospects concerning the correlation between green sukuk and sustainable development goals (SDGs).Originality – The analysis provides insights into the evolution of green sukuk, identifies gaps in current research, and highlights emerging areas of interest.